2020
DOI: 10.3390/foods9070963
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Dynamics between Yeasts and Acetic Acid Bacteria in Kombucha: Impacts on the Chemical Composition of the Beverage

Abstract: Kombucha is a traditional low-alcoholic beverage made from sugared tea and transformed by a complex microbial consortium including yeasts and acetic acid bacteria (AAB). To study the microbial interactions and their impact on the chemical composition of the beverage, an experimental design with nine couples associating one yeast strain and one AAB strain isolated from original black tea kombucha was set up. Three yeast strains belonging to the genera Brettanomyces, Hanseniaspora, and Saccharomyces and three st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
102
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 83 publications
8
102
1
3
Order By: Relevance
“…In the presence of oxygen, Brettanomyces yeasts contribute to acetic acid production [ 89 ] alongside the more obvious contribution from acetic acid bacteria [ 90 , 91 ]. In support of this, Tran et al (2020) observed that Kombucha fermentations performed by co-cultures of Hanseniaspora valbyensis and Komagataeibacter saccharivorans contained less sucrose phosphorylase activity than fermentations performed by Komagataeibacter saccharivorans and Brettanomyces bruxellensis , and were characterized by decreased production of both acetic and lactic acids [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the presence of oxygen, Brettanomyces yeasts contribute to acetic acid production [ 89 ] alongside the more obvious contribution from acetic acid bacteria [ 90 , 91 ]. In support of this, Tran et al (2020) observed that Kombucha fermentations performed by co-cultures of Hanseniaspora valbyensis and Komagataeibacter saccharivorans contained less sucrose phosphorylase activity than fermentations performed by Komagataeibacter saccharivorans and Brettanomyces bruxellensis , and were characterized by decreased production of both acetic and lactic acids [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These dynamic changes are well understood for some fermentations, such as Lambic beer [ 52 , 53 ], wine [ 54 , 55 , 56 ] and cheese [ 57 , 58 ]. Efforts to understand the microbial ecology of Kombucha have revealed a greater degree of apparent interchangeability in dominant yeast and bacterial species [ 22 ]. Better understanding of microbial community assemblies found in Kombucha SCOBY would facilitate further research into drivers of assembly patterns, and their relevance to Kombucha style.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study, performed by Tran and co-workers, presented the relationship between acetic acid bacteria (AAB) and yeasts during fermentation of kombucha. They showed that AAB stimulate S. cerevisiae yeast to produce metabolites under oxygen-limited conditions [ 32 ]. Another study, conducted by Tufariello and co-workers, was devoted to the improvement of the sensory profile of Negroamaro red wine at both the laboratory and the industrial scale using an innovative mixed starter formulation ( Saccharomyces cerevisiae NP103, Candida zemplinina 35NC1, and Lactiplantibacillus plantarum LP44).…”
Section: Introductionmentioning
confidence: 99%